The Impact of Covid-19 on the Performance of Exchange Traded Funds on Developed and Emerging Markets - Krystian M. ZAWADZKI (Communications of International Proceedings, 2021)
In this paper an endeavour was made to evaluate the impact of Covid-19 on the achievement of the investment objectives by selected ETFs in developed and emerging markets. For this purpose, the tracking errors calculated for 18 different ETFs operating on the basis of American, Asian and European stock indexes were analyzed. The time range of the research was selected in such a way as to compare the period before the pandemic(pre-Covid) and the period after the pandemic (post-Covid). The research results show that the outbreak of the coronavirus pandemic has not had a negative impact on the degree of implementation of the investment objective, regardless of the degree of market development. For each of the analyzed markets, the calculated tracking errors were not higher in the post-Covid period as compared to the pre-Covid period. In the vast majority of cases, they were even lower. This means that the management of the ETF has run smoothly in the most turbulent period of the 21st century.
Keywords: ETF; Covid-19; financial market; stock indexes